Wordventure: Petualangan Seru Mengenal Kosakata Bahasa Inggris untuk Siswa SDIT Qurratu A’yun Wahdah Islamiyah Gorontalo - Indri Wirahmi Bay; Helena Badu (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Early introduction of English vocabulary is essential for young learners, particularly at the lower primary level where students begin developing basic language awareness. This article reports a community service program entitled “Wordventure: An Engaging Vocabulary Adventure for Elementary School Students,” implemented in Grade 1 of SDIT Qurratu A’yun Wahdah Islamiyah Gorontalo. The program aimed to enhance students’ understanding of basic English vocabulary, specifically names of the days, through a playful and age-appropriate learning approach. The activities were designed using a Total Physical Response–based framework and implemented through games, movement-based activities, and visual flashcards. The program was conducted in a single 40-minute session and evaluated through classroom observation focusing on students’ participation and vocabulary performance. The findings indicate that most students were able to pronounce and sequence the names of the days more accurately and demonstrated high levels of enthusiasm, active engagement, and confidence during the learning process. The program also helped maintain students’ attention and created a positive learning atmosphere. These results suggest that game-based and movement-oriented vocabulary instruction can effectively support meaningful English learning experiences for young learners in primary school contexts.